The Way of Laryngoscope Disinfection: A Survey of Practice in Various Hospitals and Clinics - Rubaiat, Molla Md; Lateef, Kazi Ashkar; Quader, Abdul; Khurshid, Husain Md (Community Based Medical Journal, 2021)
Background and Aims: During general anaesthesia, laryngoscope is a common equipment for intubation used by anaesthesiologists. Laryngoscope has been identified as a potential source of cross infection. Though guidelines exist for appropriate disinfection practices, recent reviews suggested that current methods of disinfection areless effective and compliance is poor with the established protocols. We conducted a questionnaire-based survey to study the current disinfection practices being followed by a cross section of anaesthesiologists. Methods: A simple questionnaire containing 14 questions was distributed amongst anaesthesiologists through online as well as direct contact. Data were analyzed with percentage analysis. Results: Out of 150 anaesthesiologists, 120 submitted the completed questionnaires. Residents constituted 41% and 46% were consultants. Eighteen (12%) used only tap water for cleaning and 132 (88%) used a chemical agent after rinsing with water. Out of 132, 76 (51%) used detergent/soap solution, 29 (19%) would wash and then soak in disinfectant or germicidal agents (glutaraldehyde, povidone iodine and chlorhexidine) and 18 (12%) would wipe the blade with an alcohol swab. With respect to disinfection of laryngoscope handles, 70% respondents said they used an alcohol swab, 18% did not use any method, 9% were not aware of the method being used, while 3% did not respond. Conclusion: Our results indicate wide variation in methods of decontamination of laryngoscopes. Awareness regarding laryngoscope as a potential source of infection was high. We need to standardize and implement guidelines on a national level and make available resources which will help to improve patient safety. CBMJ 2020 January: Vol. 09 No. 01 P: 04-10